Efektivitas Implementasi Kebijakan Penyaluran Pupuk Bersubsidi Bagi Petani Di Desa Bangun Purba Kecamatan Lembah Sorik Merapi Kabupaten Mandailing Natal - Riadhotun Nur; Tunggul Sihombing (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
Subsidized fertilizer distribution is the process of distributing subsidized fertilizer from fertilizer subsidy implementers to farmers as final consumers. This study aims to determine and describe in detail the effectiveness of implementing subsidized fertilizer distribution policies for farmers in Bangun Purba Village, Lembah Sorik Merapi District, Mandailing Natal Regency. The research method used is descriptive method with a qualitative approach. Data collection techniques were carried out by interviews, observation, and documentation. The results showed that the implementation of the subsidized fertilizer distribution policy in Bangun Purba Village still needed improvement because it was not yet effective. In terms of the source approach it is still not effective because there are inadequate staff in providing information to farmers, but in terms of fulfilling facilities it is said to be effective. In the process approach, the implementation of the distribution of subsidized fertilizers is still experiencing delays, then the subsidized fertilizers that are distributed are also not in accordance with the needs of farmers, the price of subsidized fertilizers has also increased which is a difficulty for farmers. In terms of the targeting approach, the distribution of subsidized fertilizers has been effective because the retailers in Bangun Purba Village only provide subsidized fertilizers to registered farmers.